Methylenetetrahydrofolate reductase gene polymorphism and risk of type 2 diabetes mellitus. - Jian-Hong Zhong (Public Library of Science (PLoS), 2013)
Objective This review aimed to comprehensively assess the literature examining a possible link between the rs1801133 polymorphism (677C → T) in the gene encoding the methylenetetrahydrofolate reductase (MTHFR) gene and risk of type 2 diabetes mellitus (DM). Research design and methods Several research databases were systematically searched for studies examining the genotype at the rs1801133 polymorphism in healthy control individuals and individuals with type 2 DM. Genotype frequency data were examined across all studies and across subsets of studies according to ethnicity and presence of serious DM-related complications. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Results A total of 4855 individuals with type 2 DM and 5242 healthy controls from 15 countries comprising Asian, Caucasian and African ethnicities were found to satisfy the inclusion criteria and included in the review. Genotype at the rs1801133 polymorphism was not consistently associated with either increased or reduced risk of type 2 DM; the OR across all studies was 0.91 (95%CI 0.82 to 1.00) for the C- vs. T-allele, 0.88 (0.75 to 1.03) for CC vs. CT+TT, 0.82 (0.71 to 0.95) for CC vs. TT, and 1.15 (1.03 to 1.29) for TT vs. CC+CT. Similar results were found when the meta-analysis was repeated separately for each ethnic subgroup, and for subgroups with or without serious DM-related complications. Conclusions There does not appear to be compelling evidence of an association between the genotype at the rs1801133 polymorphism of the MTHFR gene and risk of type 2 DM.